Development of a neuropsychological battery for the Leukoaraiosis and Disability in the Elderly Study (LADIS): experience and baseline data - Madureira, Sofia; Verdelho, Ana; Ferro, José; Basile, Anna-Maria; Chabriat, Hugues; Erkinjuntti, Timo; Fazekas, Franz; Hennerici, Michael G.; O'brien, John; Pantoni, Leonardo; Salvadori, Emilia; Scheltens, Philip; et al. (Neuroepidemiology, 2006)
The relationship between age-related white matter changes and cognitive performance in independent elderly people is still not clear. The Leukoaraiosis and Disability in the Elderly study (LADIS) involves 11 European centers. It aims to assess the role of the age-related white matter changes as an independent factor in the transition to disability, and in cognitive performance of an independent elderly population. A comprehensive neuropsychological battery was constructed in order to harmonize the cognitive assessment across countries. Patients were evaluated at baseline and during the 3-year follow-up with the Mini-Mental State Examination, a modified version of the VADAS-Cog (Alzheimer's Dementia Assessment Scale plus tests of Delayed recall, Symbol digit, Digit span, Maze, Digit cancellation and Verbal fluency), Trail making and Stroop test. Six hundred thirty-eight patients (mean age 74 +/- 5 years; mean educational level 10 +/- 4, F/M: 351/287) were included in this study. Neuropsychological data were analyzed test by test and also grouped in three compound measures (executive, memory and speed/motor control domains). Older subjects (>74 years) performed significantly worse than younger subjects on the ADAS-Mod and on the tests of memory (t(631) = 3.25; p = 0.001), executive functions (t(581) = 4.68; p = 0.001) and speed/motor control (t(587) = 4.01; p = 0.001). Participants with higher educational level (>8 years of school) showed better performances on the compound measures for memory (t(631) = 3.25; p = 0.001), executive functions (t(581) = 4.68; p = 0.001) and speed/motor control (t(587) = 4.01; p = 0.001). Using multiple regression analysis models to study the influence of demographic variables on cognitive performance, age and education remained important variables influencing test performance. In the LADIS population baseline data, older age and lower educational levels negatively influence neuropsychological performance.